Electrode active material and method for producing said electrode active material

JP7631334B2Active Publication Date: 2025-02-18BASF SE
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2022525794
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-11-19
Filing Date
2020-10-15
Publication Date
2025-02-18
Estimated Expiration
2040-10-15

Smart Images

  • Figure 0007631334000005
    Figure 0007631334000005
  • Figure 0007631334000006
    Figure 0007631334000006
  • Figure 0007631334000007
    Figure 0007631334000007
Patent Text Reader

Abstract

A method for producing a manganese composite (oxy)hydroxide having an average particle size D50 in the range of 2 to 16 μm, (a) an aqueous solution containing salts of nickel and manganese, and optionally at least one of Al and Mg, or a transition metal other than nickel and manganese, wherein at least 50 mole % of the metal is manganese; (b) an aqueous solution of an alkali metal hydroxide, and (c) an organic acid or an alkali or ammonium salt thereof, wherein the organic acid has at least two functional groups per molecule, and at least one of the functional groups is a carboxylate group; A method comprising the step(s) of combining.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing a manganese composite (oxy)hydroxide having an average particle size D50 in the range of 2 to 16 μm, the method comprising: (a) providing an aqueous solution containing salts of nickel and manganese, and optionally at least one of Al and Mg, or a transition metal other than nickel and manganese, wherein at least 50 mole % of the metal is manganese; (b) an aqueous solution of an alkali metal hydroxide, and (c) an organic acid or an alkali or ammonium salt thereof, the organic acid having at least two functional groups per molecule, at least one of the functional groups being a carboxylate group; It includes a combining step or steps.

[0002] Additionally, the present invention relates to a precursor and a cathode active material made from the precursor. [Background technology]

[0003] Lithiated transition metal oxides are currently used as electrode active materials in lithium-ion batteries. Extensive research and development has been carried out over the past few years to improve properties such as charge density, specific energy, as well as other properties such as cycle life degradation and capacity loss that adversely affect the life or applicability of lithium-ion batteries. Further efforts are being made to improve the manufacturing methods.

[0004] Many of the electrode active materials currently under discussion are of the lithiated nickel-cobalt-manganese oxide ("NCM material") or lithiated nickel-cobalt-aluminum oxide ("NCA material") type.

[0005] In a typical process for the preparation of cathode materials for lithium-ion batteries, a so-called precursor is first formed by co-precipitation of a transition metal as a carbonate, oxide, or preferably as a hydroxide, which may or may not be basic. This precursor is then mixed with a lithium salt, such as, but not limited to, LiOH, Li2O, or especially Li2CO3, and calcined (fired) at high temperature. The lithium salt(s) can be used as hydrate(s) or in dehydrated form. The calcination or firing, also commonly referred to as thermal or heat treatment of the precursor, is usually carried out at temperatures ranging from 600 to 1,000 °C. During the heat treatment, a solid-state reaction takes place to form the electrode active material. If hydroxides or carbonates are used as precursors, the solid-state reaction is followed by removal of water or carbon dioxide. The heat treatment is carried out in a heated zone of an oven or kiln.

[0006] Much research has been done to improve various properties of cathode active materials, such as energy density, charge / discharge performance, capacity fade, etc. However, many cathode active materials suffer from limited cycle life and voltage fade, especially for many Mn-rich cathode active materials.

[0007] Certain high manganese materials having high energy density retention are disclosed in EP 3 486 980. However, the disclosed cathode active materials themselves suffer from limited energy density.

[0008] The morphology of many hydroxide-based precursors with high Mn content leaves room for improvement, see for example Wang et al., J. of Power Sources 2015, 274, 151. [Prior art documents] [Patent documents]

[0009] [Patent Document 1] EP 3 486 980 [Non-patent literature]

[0010] [Non-Patent Document 1] Wang et al., J. of Power Sources 2015, 274, 151 Summary of the Invention [Problem to be solved by the invention]

[0011] It was therefore an object of the present invention to provide a cathode active material having both high volumetric energy density and high energy density retention in addition to excellent morphology. It was further an object of the present invention to provide a method for producing a cathode active material having both high volumetric energy density and high energy density retention. It was further an object of the present invention to provide applications for a cathode active material having both high volumetric energy density and high energy density retention. [Means for solving the problem]

[0012] We have therefore found the method defined at the outset, which hereinafter is defined as the inventive method or the method according to the invention or the inventive coprecipitation. The inventive method is explained in more detail below. [Brief description of the drawings]

[0013] [Figure 1] FIG. 1 shows the X-ray diffraction pattern of Cp-CAM.1 using Cu-Kα radiation. [Diagram 2] FIG. 1 shows the X-ray diffraction pattern of p-CAM.2 using Cu-Kα radiation. [Diagram 3] FIG. 1 shows the X-ray diffraction pattern of p-CAM.3 using Cu-Kα radiation. [Figure 4] FIG. 1 shows the X-ray diffraction pattern of p-CAM.4 using Cu-Kα radiation. [Diagram 5] FIG. 1 shows the nitrogen physisorption isotherm of Cp-CAM.1. [Figure 6] FIG. 1 shows the nitrogen physisorption isotherm of p-CAM.2. [Figure 7] FIG. 1 shows the nitrogen physisorption isotherm of p-CAM.3. [Figure 8] FIG. 1 shows the nitrogen physisorption isotherm of p-CAM.4. [Figure 9] FIG. 1 shows the X-ray diffraction pattern of C-CAM.1 using Mo-Kα radiation. [Figure 10] FIG. 1 shows the X-ray diffraction pattern of CAM.2 using Mo-Kα radiation. [Figure 11] FIG. 1 shows the X-ray diffraction pattern of CAM.3 using Mo-Kα radiation. [Figure 12] FIG. 1 shows the X-ray diffraction pattern of CAM.4 using Mo-Kα radiation. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] In step (a), manganese, nickel, and optionally Co and M 1 The present invention provides a method for producing a particulate hydroxide, oxide or oxyhydroxide (abbreviated as (oxy)hydroxide) (hereinafter also referred to as "precursor") of at least one element of manganese, nickel, and optionally Co and M. 1 with an alkali metal hydroxide. The precursor may contain at least one of Al and Mg, or a transition metal other than nickel and manganese. At least 50 mol % of the metal in the precursor is manganese.

[0015] In a preferred embodiment, the manganese complex hydroxide contains a combination of a transition metal according to the general formula (I) and a further metal (Ni a Co b Mn c ) 1-d M 1 d (I) (In the formula, a is in the range of 0.20 to 0.40, preferably 0.20 to 0.35, b is in the range of 0 to 0.15; c is in the range of 0.50 to 0.75, preferably 0.60 to 0.70; d is in the range of 0 to 0.015; M 1 is selected from Al, Ti, Zr, Mo, Fe, Nb, and Mg; a+b+c=1.0).

[0016] In one embodiment of the invention, the precursor has an average particle size D50 in the range of 2 to 16 μm, preferably 6 to 15 μm. Average particle size D50 in the context of the present invention refers to the average value of the particle size based on the volume, which can be determined, for example, by light scattering.

[0017] In one embodiment of the invention, the width of the particle size distribution of the precursor (expressed as [(d90-d10) / (d50) diameter]) is at least 0.61, for example from 0.61 to 2, preferably from 0.65 to 1.5.

[0018] In one embodiment of the present invention, M 1 contains Mg in the range of 0.1 to 2.5 mol % relative to the total of the metals in the precursor.

[0019] In one embodiment of the invention, the precursor has 0.01 to 10 mol %, preferably 0.3 to 5 mol %, of anions other than hydroxide or oxide ions, based on the total number of anions, for example sulfate.

[0020] In one embodiment of the invention, the precursor comprises manganese, nickel, and optionally cobalt and M 1(solution (a)) with an aqueous solution of an alkali metal hydroxide (solution (b)) and an organic acid or its alkali or ammonium salt having at least two functional groups per molecule (c). The organic acid or its alkali or ammonium salt having at least two functional groups per molecule, also referred to as organic acid (c) or a salt of organic acid (c), respectively, may be added as such or in aqueous solution or combined with solution (a) or solution (b) in the form of a premix.

[0021] The term water-soluble salts of manganese and nickel, or of metals other than nickel and manganese, refers to salts having a solubility of 25 g / l or more in distilled water at 25° C., the amount being determined omitting water of crystallization and water resulting from aquo complexes. The water-soluble salts of nickel, cobalt and manganese are preferably Ni 2+ and Mn 2+ Examples of the water-soluble salts of nickel and manganese include sulfates, nitrates, acetates, and halides (particularly chlorides). Nitrates and sulfates are preferred, and sulfates are more preferred.

[0022] In one embodiment of the invention, the concentration of solution (a) can be selected within wide limits. Preferably, the total concentration is selected to be in the range of 1 to 1.8 moles of transition metal per kg of solution, more preferably 1.5 to 1.7 moles of transition metal per kg of solution. As used herein, "transition metal salt" refers to nickel and manganese, and, where applicable, cobalt and M. 1 and may include salts of other metals, such as magnesium or aluminum, or transition metals other than nickel and manganese.

[0023] Another example of a water-soluble salt is alum, KAl(SO4)2.

[0024] Solution (a) may have a pH value in the range of 2 to 6. In embodiments where a higher pH value is desired, ammonia may be added to solution (a). However, it is preferred not to add ammonia.

[0025] Solution (b) is an aqueous solution of an alkali metal hydroxide. Examples of alkali metal hydroxides include lithium hydroxide, with potassium hydroxide and a combination of sodium hydroxide and potassium hydroxide being preferred, and sodium hydroxide being even more preferred.

[0026] Solution (b) may contain some amount of carbonate, for example due to aging of the solution or of the respective alkali metal hydroxide.

[0027] The pH value of solution (b) is preferably greater than or equal to 13, for example 14.5.

[0028] Additionally, organic acid (c) or an alkali metal salt of organic acid (c), such as an alkali metal salt or ammonium salt of organic acid (c), is formed. The organic acid has at least two functional groups per molecule, one of which is a carboxylic acid group. Ammonia may or may not be used during the step of combining solutions (a) and (b). In such an embodiment, it is preferred to add organic acid (c) or an ammonium or alkali metal salt of organic acid (c).

[0029] The organic acid (c) or the alkali metal salt of the organic acid (c) has at least two functional groups per molecule, one of which is a carboxylic acid group, and preferably has 2 to 5 functional groups, at least one of which is a carboxylate group.

[0030] In one embodiment of the invention, the organic acid or its respective salt has at least two functional groups per molecule selected from carboxyl, hydroxyl and amino groups, at least one of which is a carboxylate group. Examples of organic acids (c) having two identical functional groups include adipic acid, oxalic acid, succinic acid and glutaric acid.

[0031] Preferably, the second functional group and, where applicable, the further functional groups are selected from carboxyl, hydroxyl and amino groups. In a preferred embodiment of the present invention, the organic acid (c) or its alkali or ammonium salts each have at least two different functional groups, of which at least one is a carboxylate group and at least one is selected from hydroxyl and amino groups.

[0032] In one embodiment of the invention, the organic acid (c) is selected from malic acid, tartaric acid, citric acid, and glycine.

[0033] In one embodiment of the invention, the pH value at the end of the step of combining solutions (a) and (b) is in the range of 8 to 12, preferably 9.5 to 12.0, measured in the mother liquor at 23° C., respectively.

[0034] In one embodiment of the present invention, the molar amount of acid (c) or its respective alkali metal salt or ammonium salt is in the range of 0.1 to 30 mol %, preferably 0.5 to 20 mol %, more preferably 0.7 to 16 mol %, based on the sum of nickel and manganese, and, where applicable, Al and Mg and transition metals other than nickel and manganese.

[0035] In one embodiment of the invention, the co-precipitation of the invention is carried out in the presence of ammonia, which may be added as solution (d) or together with any of solutions (a) and / or (b) or together with the organic acid (c). However, it is preferred that the process of the invention is carried out in the absence of ammonia.

[0036] In one embodiment of the present invention, the coprecipitation of the present invention is carried out at a temperature in the range of 10 to 85°C, preferably at a temperature in the range of 20 to 60°C.

[0037] In one embodiment of the present invention, the co-precipitation of the present invention is carried out under an inert gas, for example a noble gas such as argon, or N2.

[0038] In one embodiment of the invention, a slight excess of alkali metal hydroxide relative to nickel and manganese and any optional metals is applied, for example 0.1 to 10 mol %.

[0039] In one embodiment of the present invention, the addition of organic acid (c) or its ammonium or alkali metal salt results in a mother liquor formed in the co-precipitation of the present invention with a Mn solubility (g Mn / g water) that is at least half of the Ni solubility (g Ni / g water), more preferably at least 100% of the Ni solubility (g Ni / g water), but at most 200% of the Ni solubility (g Ni / g water).

[0040] In one embodiment of the present invention, the addition of organic acid (c) or its ammonium or alkali metal salt results in a mother liquor formed in the coprecipitation of the present invention with a Mn solubility (g Mn / g water) in the precipitation vessel of at least 2 ppm, preferably at least 10 ppm, more preferably at least 50 ppm. Preferably, the maximum solubility of Mn in the mother liquor is 3,000 ppm.

[0041] After combining solutions (a) and (b) with organic acid (c) or an alkali metal salt of organic acid (c), a slurry is formed. The solids may be separated by solid-liquid separation techniques such as decantation, filtration, centrifugation, with filtration being preferred. One or more washing steps of the solid residue are preferred.

[0042] The residue is then dried, for example under air, at a temperature in the range of 100-120° C. Preferably, the residual moisture of the precursor is less than 1% by weight, for example 0.01-0.5% by weight. The precursor is obtained from the co-precipitation of the present invention.

[0043] A further aspect of the present invention relates to a precursor for producing an electrode active material for a lithium ion battery. Specifically, the present invention relates to a particulate manganese composite (oxy)hydroxide having an average particle size (D50) in the range of 2 to 16 μm, wherein the metal moiety has the general formula: (Ni a Co b Mn c ) 1-d M 1 d (I) (In the formula, a is in the range of 0.20 to 0.40, preferably 0.20 to 0.35, b is in the range of 0 to 0.15; c is in the range of 0.50 to 0.75, preferably 0.60 to 0.70; d is in the range of 0 to 0.015; M 1 is selected from Al, Ti, Zr, Mo, Fe, Nb, and Mg; a+b+c=1.0) The manganese complex (oxy)hydroxide is 20 to 300 m 2 Specific surface area (BET) determined according to DIN ISO 9277 (2014) in the range of 0.06 to 0.5 cm / g and 3 / g, determined according to DIN 6613:19984. 2 / g and 0.1 to 0.28 cm 3 Pore ​​volumes in the range of / g are preferred.

[0044] Said manganese complex (oxy)hydroxide is hereinafter also referred to as "the precursor of the present invention" or "the precursor according to the present invention".

[0045] (Oxy)hydroxide in the context of the present invention refers not only to compounds having equal amounts of oxide and hydroxide anions, but also to hydroxides and any oxide anion-containing hydroxides of the respective metals.

[0046] Some metals are ubiquitous, e.g., sodium, calcium or zinc, and trace amounts of them are present virtually everywhere, but such trace amounts are not considered in the context of the present invention, trace amounts in this context meaning amounts of 0.05 mol % or less relative to the total metal content of the precursor of the present invention.

[0047] In a preferred embodiment of the invention, the precursor of the invention has an average particle size D50 in the range of 6 to 15 μm.

[0048] In one embodiment of the invention, the width of the particle size distribution of the precursor of the invention (expressed as [(d90-d10) / (d50) diameter]) is at least 0.61, for example from 0.61 to 2, preferably from 0.65 to 1.5.

[0049] In one embodiment of the invention, the precursor of the invention has an average pore size determined according to DIN 66134:1998 in the range of 2 to 50 nm in the range of 2 to 7.5 nm.

[0050] In one embodiment of the present invention, the X-ray diffraction pattern of the precursor of the present invention using CuKα X-rays shows a diffraction peak having a full width at half maximum (FWHM) of at least 0.4, preferably 1.0, between 2θ=7.5° and 9.5°, which diffraction peak may consist of a single diffraction peak or a convolution of at least two diffraction peaks.

[0051] The precursors of the present invention may have a unimodal or bimodal particle size distribution.

[0052] In one embodiment of the present invention, M 1 contains Mg in the range of 0.1 to 2.5 mol % relative to the total of the metals in the precursor of the present invention.

[0053] In one embodiment of the present invention, the precursor of the present invention contains 0.01 to 10 mol %, preferably 0.3 to 5 mol %, of anions other than hydroxide ions or oxide ions, such as carbonates and / or sulfates, based on the total number of anions.

[0054] The precursor of the present invention is highly suitable as a starting material for the production of electrode active materials, in particular cathode active materials for lithium-ion batteries. A further aspect of the present invention is therefore the use of the precursor of the present invention for the production of cathode active materials for lithium-ion batteries. A further aspect of the present invention is a method for the production of a cathode active material, hereinafter also referred to as the inventive production method or the production method according to the invention. Said inventive production method comprises the following steps: (α) mixing the precursor of the present invention with a lithium source (hereinafter also referred to as step (α)), and (β) A step of firing the mixture at a temperature in the range of 800 to 980° C. (hereinafter also referred to as step (β)). Includes.

[0055] In step (α), a lithium source is added to the precursor. To carry out step (α) of the method of the present invention, the procedure may be, for example, mixing the precursor with at least one lithium compound selected from Li2O, LiOH and Li2CO3, and crystallization water is ignored in the context of the present invention. A preferred lithium source is Li2CO3.

[0056] To carry out step (α), the amounts of precursor and lithium source are selected to obtain the stoichiometry of the desired inventive material. Preferably, the precursor and lithium source compound(s) contain lithium and all of the transition metals of the inventive precursor and any M that is not a transition metal. 1 The molar ratio of the total of the above to the total of the above is selected to be in the range of 1.275:1 to 1.42:1, preferably 1.30:1 to 1.38:1, and more preferably 1.32:1 to 1.36:1.

[0057] Step (α) can be carried out, for example, in a plowshare mixer or a tumble mixer. In laboratory scale experiments, a roller mill can also be applied.

[0058] To carry out step (β) of the method of the present invention, according to step (β), the obtained mixture is calcined at a temperature in the range of 800-980°C, preferably 875-950°C.

[0059] Step (β) of the process of the invention can be carried out in a furnace, such as a rotary tube furnace, a muffle furnace, a pendulum furnace, a roller hearth furnace or a push-through furnace, and also a combination of two or more of the above mentioned furnaces.

[0060] Step (β) of the method of the present invention can be carried out for a period of from 30 minutes to 24 hours, preferably from 3 to 12 hours. Step (β) can be carried out at a temperature level or a temperature profile can be performed.

[0061] In one embodiment of the present invention, step (β) is carried out in an oxygen-containing atmosphere. Oxygen-containing atmospheres include atmospheres of air, pure oxygen, a mixture of oxygen and air, and air diluted with an inert gas such as nitrogen. In step (β), an atmosphere of oxygen or oxygen diluted with air or nitrogen, and a minimum oxygen content of 5% by volume is preferred.

[0062] In one embodiment of the present invention, between steps (α) and (β), at least one pre-baking step (β * ) is being carried out. * ) involves heating the mixture obtained in step (α) at ​​a temperature in the range of 300 to 700° C. for 2 to 24 hours.

[0063] During the temperature change, a heating rate of 1 K / min to 10 K / min can be obtained, preferably 2 to 5 K / min.

[0064] After step (β), the resulting material is preferably cooled to room temperature. A cathode active material is obtained having excellent morphology and very good electrochemical properties, in particular high volumetric energy density and high energy density retention. In order to further improve the cathode active material obtained by the manufacturing method of the present invention, after step (β), the following two steps may be further carried out: (γ) The resulting lithium oxide is treated with a mineral acid or M 2 or a combination thereof, removing water; 2is selected from Al, Ti, Zr, Mo, Fe, Nb, B and Mg; and (δ) heat treating the resulting solid residue may be carried out.

[0065] In step (γ), the particulate material is 2 or a combination thereof, preferably an aqueous solution of an inorganic aluminum compound. Said aqueous solution may have a pH value ranging from 1 to 8, preferably at least 2, more preferably from 2 to 7. At the end of step (γ), the pH value of the aqueous phase is preferably observed to be in the range of 3 to 6.

[0066] Examples of mineral acids are nitric acid and especially sulfuric acid, for example at concentrations between 0.01M and 2M, preferably between 0.1 and 1.5M.

[0067] It is preferred that the water hardness, in particular calcium, of the aqueous solution used in step (γ) is at least partially removed. It is preferred to use demineralized water.

[0068] Such an M 1 The compound of formula (I) is readily soluble in water. In this context, "readily soluble" means that the compound of formula (I) is capable of dissolving in water at a concentration of at least 10 g M per 1 liter of water at 25°C. 1 This means the solubility of a compound in water.

[0069] Examples of suitable aluminum compounds are Al2(SO4)3, KAl(SO4)2 and Al(NO3)3.

[0070] An example of a suitable titanium compound is Ti(SO4)2. An example of a suitable zirconium compound is zirconium nitrate, which has the empirical formula Zr(NO3)4.

[0071] Examples of suitable molybdenum compounds are MoO3, Na2MoO4 and Li2MoO4.

[0072] Examples of suitable tungsten compounds are WO3, Na2WO4, H2WO4 and Li2WO4.

[0073] Examples of suitable magnesium compounds are MgSO4, Mg2Cl2 and Mg(NO3)2.

[0074] An example of a suitable boron compound is boric acid, which has the empirical formula H3BO3.

[0075] In one embodiment, M 2 The amount of this compound is in the range of 0.01 to 5.0 mol %, preferably 0.1 to 2.0 mol %, based on TM.

[0076] In one embodiment of the present invention, the treatment comprises the step of: 2 The reaction is carried out with a solution of this compound, for example, Al2(SO4)3 in aqueous H2SO4.

[0077] The treatment in step (γ) is carried out by adding a mineral acid or M to the cathode active material in step (β). 1 and allowing the resulting mixture to interact. Such interaction may be facilitated by stirring.

[0078] In one embodiment of the present invention, step (γ) is carried out at a temperature in the range of 5 to 85° C., preferably 10 to 60° C. Room temperature is particularly preferred.

[0079] In one embodiment of the invention, step (γ) is carried out at normal pressure. However, it is preferred to carry out step (γ) under elevated pressure, for example at a pressure between 10 mbar and 10 bar above normal pressure, or under suction, for example at a pressure between 50 and 250 mbar below normal pressure, preferably at a pressure between 100 and 200 mbar below normal pressure.

[0080] In one embodiment of the invention, step (γ) is carried out in an agitated filter apparatus, such as an agitated pressure filter or an agitated suction filter.

[0081] The material obtained from step (β) is called M 1The time for treatment with this compound may range from 2 to 60 minutes, preferably from 10 to 45 minutes.

[0082] In one embodiment of the present invention, the material obtained from step (c) is reacted with a mineral acid or M 2 The volume ratio of the compound to the solution is in the range of 1:1 to 1:10, preferably 1:1 to 1:5.

[0083] In one embodiment of the present invention, steps (γ) to (δ) are carried out in the same vessel, for example in a stirred filter apparatus, such as a stirred pressure filter or a stirred suction filter.

[0084] In one embodiment of the present invention, step (γ) is repeated, for example, 1 to 10 times. In a preferred embodiment, step (γ) is carried out only once.

[0085] Mineral acid or M 2 After treatment with the compound of formula (I), water is removed. The removal of water may be carried out by evaporation or, preferably, by a solid-liquid separation method, for example, by decantation, or by any type of filtration, for example, on a band filter or in a filter press. The removal of water may involve complete or partial removal of water, with partial removal being preferred. Together with the water, mineral acid and / or M 1 And / or non-precipitated compounds of lithium salts can also be removed. A residue is obtained which can contain 0.01 to 5% by mass of residual moisture.

[0086] In one embodiment of the present invention, the filter media may be selected from ceramics, sintered glass, sintered metals, organic polymer films, nonwoven fabrics, and woven fabrics.

[0087] In step (δ), the residue is heat treated.

[0088] Step (δ) can be carried out in any type of oven, such as a roller hearth kiln, a pusher kiln, a rotary kiln, a pendulum kiln, or, in the case of laboratory scale tests, a muffle oven.

[0089] The temperature of the heat treatment in step (δ) may be in the range of 150 to 290°C, or 300 to 500°C.

[0090] The temperature of 300 to 500° C. corresponds to the maximum temperature in step (δ).

[0091] It is possible that the material obtained from step (γ) can be directly subjected to step (δ), however it is preferred to increase the temperature stepwise or gradually, or to first dry the material obtained after step (γ) at a temperature in the range of 40-80° C. before subjecting it to step (δ).

[0092] The stepwise or gradual increase can be carried out under normal pressure or reduced pressure, for example at a pressure of 1 to 500 mbar.

[0093] The maximum temperature step (δ) is carried out under normal pressure.

[0094] In one embodiment of the invention, step (δ) is carried out under an oxygen-containing atmosphere, such as air, oxygen-enriched air or pure oxygen.

[0095] In embodiments where drying is carried out prior to step (δ) at a temperature in the range of 100-250° C., such drying may be carried out for a duration of 10 minutes to 12 hours.

[0096] In one embodiment of the present invention, step (δ) is carried out under an atmosphere having a reduced CO2 content, for example, a carbon dioxide content in the range of 0.01 to 500 ppm by mass, preferably 0.1 to 50 ppm by mass. The CO2 content can be determined, for example, by optical methods using infrared light. It is even more preferred to carry out step (e) under an atmosphere having a carbon dioxide content below the detection limit of, for example, optical methods based on infrared light.

[0097] In one embodiment of the present invention, step (δ) has a duration ranging from 1 to 10 hours, preferably from 90 minutes to 6 hours.

[0098] In one embodiment of the present invention, the lithium content of the electrode active material is reduced by 1-5% by mass, preferably 2-4% by mass, said reduction mainly affecting the so-called residual lithium.

[0099] By carrying out the method of the present invention, an electrode active material having superior electrochemical properties is obtained. Without wishing to be bound by any theory, it is hypothesized that the excess aluminum leads to the removal of lithium compounds that have accumulated on the surface of the electrode active material.

[0100] Without wishing to be bound by any theory, it is hypothesized that the method of the present invention results in alteration of the surface of particles of the material of the present invention.

[0101] The process of the present invention may comprise optional additional steps, such as a rinsing step after step (γ) or a sieving step after step (δ).

[0102] A further aspect of the present invention relates to a cathode active material, hereinafter also referred to as the cathode active material of the present invention. The cathode active material of the present invention can be obtained according to the manufacturing method of the present invention.

[0103] The cathode active material of the present invention is defined in more detail below.

[0104] The cathode active material of the present invention has an average particle size (D50) in the range of 2 to 16 μm and a composition Li 1+x TM 1-x O2, where x is in the range of 0.1 to 0.2, and TM is a combination of elements according to general formula (II), and the metal moiety has the general formula: (Ni a Co b Mn c ) 1-d-e M 1 d M 2 e (II) (In the formula, a is in the range of 0.20 to 0.40, preferably 0.20 to 0.35, b is in the range of 0 to 0.15; c is in the range of 0.50 to 0.75, preferably 0.60 to 0.70; d is in the range of 0 to 0.015; e is in the range of 0 to 0.15; M 1 is selected from Al, Ti, Zr, Mo, Fe, Nb, and Mg; M 2 is selected from Al, Ti, Zr, Mo, Fe, Nb, B, W, and Mg; a+b+c=1.0) The composite oxide is 0.5 m 2 / g~10m 2 / g, and a specific surface area (BET), hereinafter also referred to as BET surface area, of at least 2.7 g / cm 3 , preferably 2.72 to 3.1 g / cm 3 , more preferably 2.80 to 3.00 g / cm 3 The pressed density is determined at a pressure of 250 MPa. The BET surface area can be determined by nitrogen adsorption after outgassing the sample at 200° C. for 30 minutes and beyond, according to DIN ISO 9277:2010.

[0105] In a preferred embodiment, the structural distortion is 0.8% or less, preferably 0.6% or less, at the reflection peak between 29.8 and 30.6° in the corresponding X-ray diffraction pattern using Mo-Kα X-rays. The structural distortion can be determined from the corresponding diffraction pattern by the Rietveld method.

[0106] Lithium-ion batteries comprising at least one electrode according to the invention exhibit very good discharge and cycling behavior and good safety behavior.

[0107] In one embodiment of the present invention, the cathode of the present invention comprises (A) at least one substance of the invention as defined above, (B) carbon in a conductive state, and (C) binder, (D) Current collector Contains:

[0108] In a preferred embodiment of the present invention, the cathode of the present invention comprises, based on the sum of (A), (B) and (C), (A) 80 to 99% by mass of the substance of the present invention; (B) 0.5 to 19.5 mass% carbon, (C) 0.5 to 9.5% by mass of a binder material Contains:

[0109] The cathode according to the invention contains a conductive modified carbon, also called carbon (B) for short. Carbon (B) can be selected from soot, activated carbon, carbon nanotubes, graphene and graphite. Carbon (B) can be added directly during the preparation of the electrode material according to the invention.

[0110] The electrodes according to the invention may contain further components. They may contain a current collector (D), for example (but not limited to) an aluminum foil. They may further contain a binder material (C), also called binder (C) below. The current collector (D) will not be described further here.

[0111] Suitable binders (C) are preferably selected from organic (co)polymers. Suitable (co)polymers, i.e. homopolymers or copolymers, can be selected, for example, from (co)polymers obtainable by anionic, catalytic or free radical (co)polymerization, in particular from polyethylene, polyacrylonitrile, polybutadiene, polystyrene and copolymers of at least two comonomers selected from ethylene, propylene, styrene, (meth)acrylonitrile and 1,3-butadiene. Polypropylene is also suitable. Polyisoprene and polyacrylates are furthermore suitable. Polyacrylonitrile is particularly preferred.

[0112] In the context of the present invention, polyacrylonitrile is understood to mean not only polyacrylonitrile homopolymers but also copolymers of acrylonitrile with 1,3-butadiene or with styrene. Polyacrylonitrile homopolymers are preferred.

[0113] In the context of the present invention, polyethylene refers not only to homopolyethylenes, but also to copolymerized ethylene with at least 50 mol % and up to 50 mol % of at least one further comonomer, such as α-olefins, such as propylene, butylene (1-butene), 1-hexene, 1-octene, 1-decene, 1-dodecene, 1-pentene, and also isobutene, vinyl aromatics, such as styrene, and also (meth)acrylic acid, vinyl acetate, vinyl propionate, C1-C2 copolymers of (meth)acrylic acid. 10 -alkyl esters, in particular methyl acrylate, methyl methacrylate, ethyl acrylate, ethyl methacrylate, n-butyl acrylate, 2-ethylhexyl acrylate, n-butyl methacrylate, 2-ethylhexyl methacrylate, and also copolymers of ethylene with maleic acid, maleic anhydride and itaconic anhydride. The polyethylene may be HDPE or LDPE.

[0114] In the context of the present invention, polypropylene is understood to mean not only homopolypropylene but also copolymers of propylene with at least 50 mol % copolymerized propylene and up to 50 mol % of at least one further comonomer, such as ethylene, and α-olefins, such as butylene, 1-hexene, 1-octene, 1-decene, 1-dodecene and 1-pentene. The polypropylene is preferably isotactic polypropylene or essentially isotactic polypropylene.

[0115] In the context of the present invention, polystyrene refers not only to homopolymers of styrene, but also to C1-C4 copolymers of acrylonitrile, 1,3-butadiene, (meth)acrylic acid, and (meth)acrylic acid. 10-alkyl esters, divinylbenzene, in particular 1,3-divinylbenzene, 1,2-diphenylethylene and α-methylstyrene copolymers are also understood to mean.

[0116] Another preferred binder (C) is polybutadiene.

[0117] Other suitable binders (C) are selected from polyethylene oxide (PEO), cellulose, carboxymethyl cellulose, polyimides and polyvinyl alcohol.

[0118] In one embodiment of the invention, the binder (C) has an average molecular weight M ranging from 50,000 g / mol to 1,000,000 g / mol, preferably up to 500,000 g / mol. W The (co)polymers are selected from those having the formula:

[0119] The binder (C) may be a crosslinked or non-crosslinked (co)polymer.

[0120] In a particularly preferred embodiment of the present invention, the binder (C) is selected from halogenated (co)polymers, in particular fluorinated (co)polymers.Halogenated or fluorinated (co)polymers are understood to mean (co)polymers that contain at least one (co)polymerized (co)monomer with at least one halogen atom or at least one fluorine atom per molecule, more preferably at least two halogen atoms or at least two fluorine atoms per molecule.Examples include polyvinyl chloride, polyvinylidene chloride, polytetrafluoroethylene, polyvinylidene fluoride (PVdF), tetrafluoroethylene-hexafluoropropylene copolymer, vinylidene fluoride-hexafluoropropylene copolymer (PVdF-HFP), vinylidene fluoride-tetrafluoroethylene copolymer, perfluoroalkyl vinyl ether copolymer, ethylene-tetrafluoroethylene copolymer, vinylidene fluoride-chlorotrifluoroethylene copolymer, and ethylene-chlorofluoroethylene copolymer.

[0121] Suitable binders (C) are especially polyvinyl alcohol and halogenated (co)polymers such as polyvinyl chloride or polyvinylidene chloride, especially fluorinated (co)polymers such as polyvinyl fluoride and especially polyvinylidene fluoride and polytetrafluoroethylene.

[0122] The electrode of the present invention may contain 0.5 to 9.5 mass % of binder(s) (C) based on the total of component (A), carbon (B) and binder (C).

[0123] A further aspect of the present invention is (A) at least one cathode comprising the material of the present invention (A), carbon (B) and a binder (C); (B) at least one anode; and (C) at least one electrolyte It is a battery containing

[0124] The embodiment of the cathode (1) has already been described in detail above.

[0125] The anode (2) may contain at least one anode active material, such as carbon (graphite), TiO2, lithium titanium oxide, silicon, or tin. The anode (2) may further contain a current collector, such as a metal foil, such as copper foil.

[0126] The electrolyte (3) may include at least one non-aqueous solvent, at least one electrolyte salt, and optionally additives.

[0127] The non-aqueous solvent for the electrolyte (3) may be liquid or solid at room temperature and is preferably selected from polymers, cyclic or acyclic ethers, cyclic and acyclic acetals, and cyclic or acyclic organic carbonates.

[0128] Examples of suitable polymers are in particular polyalkylene glycols, preferably poly-C1-C4-alkylene glycols and in particular polyethylene glycols, where the polyethylene glycols may contain up to 20 mol % of one or more C1-C4-alkylene glycols.The polyalkylene glycols are preferably polyalkylene glycols with two methyl or ethyl end caps.

[0129] The molecular weight M of suitable polyalkylene glycols, particularly suitable polyethylene glycols, W may be at least 400 g / mol.

[0130] The molecular weight M of suitable polyalkylene glycols, particularly suitable polyethylene glycols, W can be up to 5,000,000 g / mol, preferably up to 2,000,000 g / mol.

[0131] Examples of suitable acyclic ethers are, for example, diisopropyl ether, di-n-butyl ether, 1,2-dimethoxyethane, 1,2-diethoxyethane, with 1,2-dimethoxyethane being preferred.

[0132] Examples of suitable cyclic ethers are tetrahydrofuran and 1,4-dioxane.

[0133] Examples of suitable acyclic acetals are, for example, dimethoxymethane, diethoxymethane, 1,1-dimethoxyethane and 1,1-diethoxyethane.

[0134] An example of a suitable cyclic acetal is 1,3-dioxane, and especially 1,3-dioxolane.

[0135] Examples of suitable acyclic organic carbonates are dimethyl carbonate, ethyl methyl carbonate, and diethyl carbonate.

[0136] Examples of suitable cyclic organic carbonates are compounds of the general formulae (IIIa) and (IIIb) [ka] (In the formula, R 1 , R 2 and R 3 can be the same or different and are selected from hydrogen and C1-C4-alkyl, such as methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, sec-butyl and tert-butyl, preferably R 2 and R 3 (Both cannot be tert-butyl).

[0137] In a particularly preferred embodiment, R 1 is methyl, R 2 and R 3 are each hydrogen or R 1 , R 2 and R 3 are hydrogen.

[0138] Another preferred cyclic organic carbonate is vinylene carbonate of formula (IV).

[0139] [ka]

[0140] Preferably, the solvent or solvents are used in an aqueous state, ie with a water content in the range of 1 ppm to 0.1% by weight, which can be determined, for example, by Karl Fischer titration.

[0141] The electrolyte (3) further comprises at least one electrolyte salt. Suitable electrolyte salts are in particular lithium salts. Examples of suitable lithium salts are LiPF6, LiBF4, LiClO4, LiAsF6, LiCF3SO3, LiC(C n F 2n+1 SO2)3, lithium imide, e.g. LiN(C n F 2n+1 SO2)2 (wherein n is an integer ranging from 1 to 20), LiN(SO2F)2, Li2SiF6, LiSbF6, LiAlCl4, and compounds of the general formula (C n F 2n+1 SO2) t It is the salt of YLi. where t=1 when Y is selected from oxygen and sulfur; when Y is selected from nitrogen and phosphorus, t=2; When Y is selected from carbon and silicon, t=3).

[0142] Preferred electrolyte salts are selected from LiC(CF3SO2)3, LiN(CF3SO2)2, LiPF6, LiBF4, LiClO4, with LiPF6 and LiN(CF3SO2)2 being particularly preferred.

[0143] In a preferred embodiment of the present invention, the electrolyte (3) contains at least one flame retardant. Useful flame retardants may be selected from trialkyl phosphates (wherein the alkyls are different or the same), triaryl phosphates, alkyl dialkyl phosphonates, and halogenated trialkyl phosphates. Preferred are tri-C1-C4-alkyl phosphates (wherein the C1-C4-alkyls are different or the same), tribenzyl phosphate, triphenyl phosphate, C1-C4-alkyl di-C1-C4-alkyl phosphonates, and fluorinated tri-C1-C4-alkyl phosphates.

[0144] In a preferred embodiment, the electrolyte (3) comprises at least one flame retardant selected from trimethyl phosphate, CH3-P(O)(OCH3)2, triphenyl phosphate, and tris-(2,2,2-trifluoroethyl)-phosphate.

[0145] The electrolyte (3) may contain 1 to 10 mass % of a flame retardant based on the total mass of the electrolyte.

[0146] In an embodiment of the invention, the battery according to the invention comprises one or more separators (4) by means of which the electrodes are mechanically separated. Suitable separators (4) are polymer films, in particular porous polymer films, which are unreactive towards metallic lithium. Particularly suitable materials for the separators (4) are polyolefins, in particular film-forming porous polyethylene and film-forming porous polypropylene.

[0147] The separator (4) made of polyolefin, particularly polyethylene or polypropylene, can have a porosity in the range of 35 to 50%. The suitable pore size is, for example, in the range of 30 to 500 nm.

[0148] In another embodiment of the present invention, the separator (4) can be selected from PET nonwoven fabrics filled with inorganic particles. Such separators can have a porosity in the range of 40-55%. Suitable pore sizes are, for example, in the range of 80-750 nm.

[0149] The battery according to the invention further comprises a housing which may have any shape, for example a cube or a cylindrical disk.In one variant, a metal foil configured as a pouch is used as the housing.

[0150] The battery according to the invention exhibits very good discharge and cycling behaviour, especially with regard to capacity loss, especially at high temperatures (above 45° C., for example below 60° C.).

[0151] The battery according to the present invention may comprise two or more electrochemical cells that are combined with each other, for example, connected in series or connected in parallel. A series connection is preferred. In the battery according to the present invention, at least one electrochemical cell contains at least one cathode according to the present invention. Preferably, in the electrochemical cell according to the present invention, the majority of the electrochemical cells contain the cathode according to the present invention. Even more preferably, in the battery according to the present invention, all the electrochemical cells contain the cathode according to the present invention.

[0152] The present invention further provides a method for using the battery according to the present invention in equipment, especially mobile equipment.Examples of mobile equipment are vehicles, such as automobiles, bicycles, aircraft, or water vehicles, such as boats or ships.Other examples of mobile equipment are manually operated, such as computers, especially laptops, phones, or powered hand tools, for example in the construction sector, especially drills, battery-powered drivers, or battery-powered staplers.

[0153] The present invention is further illustrated by examples. EXAMPLES

[0154] Unless otherwise stated, percentages are by weight.

[0155] The strains were obtained by the Rietveld method using the modeling software DIFFRAC.TOPAS from Bruker AXS GmbH, Karlsruhe.

[0156] Preparation of comparative precursor Cp-CAM.1 Step (a.1): In a continuous stirred tank reactor of volume V=2.4 l at 50° C. under nitrogen atmosphere, an aqueous MnSO4 / NiSO4 mixture solution having concentrations c1(Mn)=1.10 mol / kg and c1(Ni)=0.55 mol / kg (also referred to as solution 1) was combined with a 25% by weight aqueous NaOH solution (also referred to as solution 2) and a 25% aqueous ammonia (NH3) solution (also referred to as solution 3). Solutions 2 and 3 were mixed before being added to the reactor. i (where i represents the number of the corresponding solution) The flow rate of each solution is expressed as res = V / (f1 + f2 + f3) = 5 hours, pH value in the reactor of 11.5, and c R (NH3) / (c R (Ni)+c R (Mn)) = 0.4 (where c R (NH3), c R (Ni) and c R The reactor was adjusted to fill the 1000 ml of ammonium hydroxide (Mn) and 1000 ml of manganese (Mn) (where Mn is the concentration of ammonia, nickel and manganese in mol / kg). A stirrer with two crossed blades was applied, and the stirring speed was 850 rpm. The particles of Cp-CAM.1 were precipitated in the reactor and transferred to a second vessel by continuous flow through the outlet for collection. The freshly precipitated particles were then washed with deionized water at room temperature, dried under air at 120° C. for 12 hours, and sieved to obtain the precursor Cp-CAM.1 with an average diameter (d50): 9.7 μm.

[0157] Preparation of comparative cathode active material C-CAM.1 Step (b.1): The precursor Cp-CAM.1 was subsequently mixed with Li2CO3 monohydrate in a molar ratio of 1.31:1 Li:(Mn+Ni), poured into an alumina crucible and calcined at 900 °C for 5 h under oxygen atmosphere (10 exchanges / h) using a heating rate of 2 °C / min. The resulting material was cooled to room temperature with a cooling rate of 10 °C / min and then sieved with a mesh size of 32 μm. After sieving, the resulting material was stirred in a beaker with 80 mL of H2SO4 (0.1 M) aqueous solution for 20 min. The liquid phase was then removed by filtration and the filter cake was rinsed with 80 mL of H2O. The filter cake was then again stirred in a beaker with 80 mL of H2SO4 (0.1 M) aqueous solution for another 20 min. The liquid phase was removed by filtration and the filter cake was washed twice with 80 mL of H2O. The resulting filter cake was dried in vacuum at 65° C. for 3 h, then dried at 300° C. for 16 h, and cooled to room temperature to obtain C-CAM.1.

[0158] Preparation of precursor p-CAM.2 Step (a.2): In a continuous stirred tank reactor of volume V=2.4 l at 60° C. under nitrogen atmosphere, an aqueous MnSO4 / NiSO4 mixture solution having concentrations c1(Mn)=1.10 mol / kg and c1(Ni)=0.55 mol / kg (also referred to as solution 1) was combined with an aqueous 25% by weight NaOH solution (also referred to as solution 2), an aqueous 25% ammonia (NH3) solution (also referred to as solution 3), and an aqueous trisodium citrate solution having a concentration of c4(citrate)=1.2 mol / kg (also referred to as solution 4). Solutions 2 and 3 were premixed before being added to the reactor. i (where i represents the number of the corresponding solution) The flow rate of each solution is expressed as res = V / (f1 + f2 + f3 + f4) = 5 hours, pH value in the reactor of 11.1, and c R (NH3) / (c R (Ni)+c R (Mn))=0.03 and c R (Citrate) / (c R (Ni)+c R (Mn)) = 0.12 (where c R (NH3), c R (Citrate), cR (Ni), c R The reactor was adjusted to fill the 1000° C. / min reactor (Mn) with the concentration of ammonia, citrate, nickel and manganese in mol / kg). A stirrer with two crossed blades was applied, and the stirring speed was 850 rpm. The particles of p-CAM.2 were precipitated in the reactor and transferred to a second vessel by continuous flow through the outlet for collection. The freshly precipitated particles were then washed with deionized water at room temperature, dried under air at 120° C. for 12 hours and sieved to obtain precursor p-CAM.2 with an average diameter (d50) of 7.1 μm.

[0159] Preparation of cathode active material CAM.2 Step (b.2): The precursor p-CAM.2 was subsequently mixed with Li2CO3 monohydrate in a molar ratio of 1.31:1 Li:(Mn+Ni), poured into an alumina crucible and heated at 900 °C for 5 h under oxygen atmosphere (10 exchanges / h) using a heating rate of 2 °C / min. The resulting material was cooled to room temperature with a cooling rate of 10 °C / min and then sieved with a mesh size of 32 μm. After sieving, the resulting material was stirred in a beaker with 80 mL of H2SO4 (0.1 M) aqueous solution for 20 min. The liquid phase was then removed by filtration and the filter cake was rinsed with 80 mL of H2O. The filter cake was then again stirred in a beaker with 80 mL of H2SO4 (0.1 M) aqueous solution for another 20 min. The liquid phase was removed by filtration and the filter cake was washed twice with 80 mL of H2O. The resulting filter cake was dried in vacuum at 65° C. for 3 hours, then dried at 300° C. for 16 hours, and cooled to room temperature to obtain CAM.2.

[0160] Preparation of precursor p-CAM.3 Step (a.3): In a continuous stirred tank reactor of volume V=2.4 l at 50° C. under nitrogen atmosphere, a mixed aqueous solution of MnSO4 / NiSO4 having concentrations c1(Mn)=1.10 mol / kg and c1(Ni)=0.55 mol / kg (also referred to as solution 1) was combined with a 25% by weight aqueous solution of NaOH (also referred to as solution 2), a 25% aqueous solution of ammonia (NH3) (also referred to as solution 3), and an aqueous solution of sodium tartrate having a concentration of c5(tartrate)=1.2 mol / kg (also referred to as solution 5). Solutions 2 and 3 were premixed before being added to the reactor. i (where i represents the number of the corresponding solution) The flow rate of each solution is expressed as res = V / (f1 + f2 + f3 + f5) = 5 hours, pH value in the reactor of 11.5, and c R (NH3) / (c R (Ni)+c R (Mn))=0.03 and c R (tartrate) / (c R (Ni)+c R (Mn)) = 0.12 (where c R (NH3), c R (tartrate), c R (Ni), c R The reactor was adjusted to fill the 1000° C. / min reactor (where Mn is the concentration of ammonia, citrate, nickel and manganese in mol / kg). A stirrer with two crossed blades was applied. The stirring speed was 850 rpm. The particles were precipitated in the reactor and transferred to a second vessel by continuous flow through the outlet for collection. The freshly precipitated particles were then washed with deionized water at room temperature, dried under air at 120° C. for 12 hours and sieved to obtain precursor p-CAM.3 with an average diameter of 4.8 μm.

[0161] Preparation of cathode active material CAM.3 Step (b.3): The precursor p-CAM.3 was subsequently mixed with Li2CO3 monohydrate in a molar ratio of 1.31:1 Li:(Mn+Ni), poured into an alumina crucible and heated at 900 °C for 5 h under oxygen atmosphere (10 exchanges / h) using a heating rate of 2 °C / min. The resulting material was cooled to room temperature with a cooling rate of 10 °C / min and then sieved with a mesh size of 32 μm. After sieving, the resulting material was stirred in a beaker with 80 mL of H2SO4 (0.1 M) aqueous solution for 20 min. The liquid phase was then removed by filtration and the filter cake was rinsed with 80 mL of H2O. The filter cake was then again stirred in a beaker with 80 mL of H2SO4 (0.1 M) aqueous solution for another 20 min. The liquid phase was removed by filtration and the filter cake was washed twice with 80 mL of H2O. The resulting filter cake was dried in vacuum at 65° C. for 3 hours, then dried at 300° C. for 16 hours, and cooled to room temperature to obtain CAM.3.

[0162] Preparation of precursor p-CAM.4 Step (a.4): In a continuous stirred tank reactor of volume V=2.4 l at 50° C. under nitrogen atmosphere, a mixed aqueous solution of MnSO4 / NiSO4 having concentrations c1(Mn)=1.10 mol / kg and c1(Ni)=0.55 mol / kg (also referred to as solution 1) was combined with a 25% by weight aqueous solution of NaOH (also referred to as solution 2), a 25% aqueous solution of ammonia (NH3) (also referred to as solution 3), and an aqueous solution of oxalic acid having a concentration of c6(oxalic acid)=0.7 mol / kg (also referred to as solution 6). Solutions 2 and 3 were premixed before being added to the reactor. i (where i represents the number of the corresponding solution) The flow rate of each solution is expressed as res = V / (f1 + f2 + f3 + f6) = 5 hours, pH value in the reactor of 11.3, and c R (NH3) / (c R (Ni)+c R (Mn))=0.03 and c R (oxalate) / (c R (Ni)+c R (Mn)) = 0.12 (where c R (NH3), c R (tartrate), c R(Ni), c R The reactor was adjusted to fill the 1000° C. / min reaction vessel (where (Mn) is the concentration of ammonia, citrate, nickel and manganese in mol / kg). A stirrer with two crossed blades was applied, and the stirring speed was 850 rpm. Particles with a given size were precipitated in the reactor and transferred to a second vessel by continuous flow through the outlet for collection. The freshly precipitated particles were then washed with deionized water at room temperature, dried under air at 120° C. for 12 h, and sieved to obtain precursor p-CAM.4.

[0163] Preparation of cathode active material CAM.4 Step (b.4): The precursor p-CAM.4 was mixed with Li2CO3 monohydrate in a molar ratio of 1.31:1 Li:(Mn+Ni), poured into an alumina crucible and calcined at 900 °C for 5 h under oxygen atmosphere (10 exchanges / h) using a heating rate of 2 °C / min. The resulting material was cooled to room temperature with a cooling rate of 10 °C / min and then sieved with a mesh size of 32 μm. After sieving, the resulting material was stirred in a beaker with 80 mL of H2SO4 (0.1 M) aqueous solution for 20 min. The liquid phase was then removed by filtration and the filter cake was rinsed with 80 mL of H2O. The filter cake was then stirred again in a beaker with 80 mL of H2SO4 (0.1 M) aqueous solution for another 20 min. The liquid phase was removed by filtration and the filter cake was washed twice with 80 mL of H2O. The resulting filter cake was dried in vacuum at 65° C. for 3 hours, then dried at 300° C. for 16 hours, and cooled to room temperature to give CAM.4 with an average diameter (d50) of 20.0 μm.

[0164] The properties of the precursors are summarized in Table 1, and the properties of the cathode active materials are summarized in Table 2.

[0165] [Table 1]

[0166] FWHM represents the full width at half maximum of the diffraction peak between 2θ = 7.5 ° and 9.5 ° of the corresponding diffraction pattern measured with Cu-Kα radiation. This diffraction peak can consist of a single diffraction peak or of a convolution of at least two diffraction peaks. Based on nitrogen physisorption measurements of the different precursors, the BET surface area was determined according to DIN ISO 9277, the mesopore volume was determined according to DIN 66134, and the average pore diameter, determined according to DIN 66134, was in the range of 2-50 nm.

[0167] Preparation of precursor p-CAM.5 Step (a.5): In a continuous stirred tank reactor of volume V=2.4 l at 60° C. under nitrogen atmosphere, an aqueous MnSO4 / NiSO4 / Al2(SO4)3 mixture solution having concentrations c1(Mn)=1.10 mol / kg, c1(Ni)=0.55 mol / kg, and c1(Al)=0.008 mol / kg (also referred to as solution 1) was combined with an aqueous 25% by weight NaOH solution (also referred to as solution 2), an aqueous 25% ammonia (NH3) solution (also referred to as solution 3), and an aqueous trisodium citrate solution having a concentration of c4(citrate)=1.2 mol / kg (also referred to as solution 4). Solutions 2 and 3 were premixed before being added to the reactor. i (where i represents the number of the corresponding solution) The flow rate of each solution is expressed as res = V / (f1 + f2 + f3 + f4) = 5 hours, pH value in the reactor of 11.3, and c R (NH3) / (c R (Ni)+c R (Mn))=0.03 and c R (Citrate) / (c R (Ni)+c R (Mn)) = 0.12 (where c R (NH3), c R (Citrate), c R (Ni), c RThe reactor was adjusted to fill the 1000° C. / min reactor (Mn) with the concentration of ammonia, citrate, nickel and manganese in mol / kg). A stirrer with two crossed blades was applied, and the stirring speed was 850 rpm. The particles of p-CAM.5 were precipitated in the reactor and transferred to a second vessel by continuous flow through the outlet for collection. The freshly precipitated particles were then washed with deionized water at room temperature, dried under air at 120° C. for 12 hours and sieved to obtain precursor p-CAM.5 with an average diameter (d50) of about 5 μm.

[0168] Preparation of cathode active material CAM.5 Step (b.5): The precursor p-CAM.5 was subsequently mixed with Li2CO3 monohydrate in a molar ratio of 1.31:1 Li:(Mn+Ni+Al), poured into an alumina crucible and heated at 900 °C for 5 h under oxygen atmosphere (10 exchanges / h) using a heating rate of 2 °C / min. The resulting material was cooled to room temperature with a cooling rate of 10 °C / min and then sieved with a mesh size of 32 μm. After sieving, the material was stirred in a beaker with 80 mL of H2SO4 (0.1 M) aqueous solution for 20 min. The liquid phase was then removed by filtration and the filter cake was rinsed with 80 mL of H2O. The filter cake was then again stirred in a beaker with 80 mL of H2SO4 (0.1 M) aqueous solution for another 20 min. The liquid phase was removed by filtration and the filter cake was washed twice with 80 mL of H2O. The resulting filter cake was dried in vacuum at 65 °C for 3 h, then dried at 300 °C for 16 h, and cooled to room temperature to obtain CAM.5. Electrodes made with CAM.5 show excellent properties, similar to those made with CAM.2 to CAM.4.

[0169] [Table 2]

[0170] The structural distortion was determined by the Rietveld method at the reflection peaks between 29.8 and 30.6° in the corresponding X-ray diffraction pattern using Mo-Kα X-rays.

[0171] Electrode fabrication: The electrodes contained 92.5% CAM, 2% carbon black (Super C65), 2% graphite (SFG6L), and 3.5% binder (polyvinylidene fluoride, Solef 5130). The slurry was mixed in N-methyl-2-pyrrolidone and cast onto aluminum foil with a doctor blade. The electrodes were dried at 105°C under vacuum for 6 hours, after which circular electrodes were punched out, weighed, and dried at 120°C under vacuum for 12 hours before being placed in an Ar-filled glove box.

[0172] Half-cell electrochemical measurements: A coin-type electrochemical cell was assembled in an argon-filled glove box. A 14 mm diameter positive electrode (loading 8.0 ± 0.5 mg cm) was -2 ) was separated from the 0.58 thick Li foil with a glass fiber separator (Whatman GF / D). A volume of 95 μl of 1 M LiPF6 in a 2:8 mass ratio of fluoroethylene carbonate (FEC):diethyl carbonate (DEC) was used as the electrolyte. The cell was galvanostatically cycled in a Maccor 4000 battery cycler between 2.0 and 4.8 V at room temperature by applying a C-rate of 0.067 C.

Claims

1. A method for producing a manganese complex (oxy)hydroxide having an average particle size D50 in the range of 2 to 16 μm, comprising the steps of: (a) providing an aqueous solution containing salts of nickel and manganese, and optionally at least one of Al and Mg, or a transition metal other than nickel and manganese, wherein at least 50 mole % of the metal is manganese; (b) an aqueous solution of an alkali metal hydroxide, and (c) an organic acid or an alkali or ammonium salt thereof, the organic acid having at least two functional groups per molecule, at least one of the functional groups being a carboxylate group; comprising the step(s) of combining, The manganese complex (oxy)hydroxide is represented by the general formula (I) (Ni a Co b Mr c ) 1-d M 1 d (I) (wherein a is in the range of 0.20 to 0.40; b is in the range of 0 to 0.15; c is in the range of 0.50 to 0.75; d is in the range of 0 to 0.015; M 1 is selected from Al, Ti, Zr, Mo, Fe, Nb, and Mg; a + b + c = 1.0) and The combining step is carried out under an inert gas selected from a noble gas and N2; method.

2. 2. The method of claim 1, wherein the organic acid or its alkali or ammonium salt has at least two different functional groups, one of which is a carboxylate group and the other of which is selected from a hydroxyl group and an amino group.

3. 3. The method according to claim 1 or 2, wherein the organic acid is selected from malic acid, tartaric acid, citric acid and glycine.

4. A particulate manganese composite (oxy)hydroxide having an average particle size (D50) in the range of 2 to 16 μm, wherein the metal portion has the following general formula: (Ni a Co b Mr c ) 1-d M 1 d (I) (wherein a is in the range of 0.20 to 0.40; b is in the range of 0 to 0.15; c is in the range of 0.50 to 0.75; d is in the range of 0 to 0.015; M 1 is selected from Al, Ti, Zr, Mo, Fe, Nb, and Mg; a + b + c = 1.0) The composite (oxy)hydroxide has a thickness of 20 to 300 m 2 / g and 0.06-0.5 cm 3 / g range of mesopore volume, determined according to DIN 66134:1998.

5. 5. The complex (oxy)hydroxide according to claim 4, having an average pore size, determined according to DIN 66134:1998 in the range of 2 to 50 nm, in the range of 2 to 7.5 nm.

6. 6. The composite (oxy)hydroxide according to claim 4 or 5, having an X-ray diffraction pattern using CuKα X-rays having a diffraction peak between 2θ=7.5° and 9.5° having a full width at half maximum (FWHM) of at least 0.4, said diffraction peak being capable of being composed of a single diffraction peak or a convolution of at least two diffraction peaks.

7. The following steps: (α) mixing the manganese composite (oxy)hydroxide according to any one of claims 4 to 6 with a lithium source; (β) firing the mixture at a temperature in the range of 800 to 980° C. (γ) contacting the resulting lithiated oxide with a mineral acid or an aqueous solution of a compound of M 2 or a combination thereof to remove water, where M 2 is selected from Al, Ti, Zr, Mo, Fe, Nb, B and Mg; and (δ) heat treating the resulting solid residue 1. A method for making a cathode active material for a lithium ion battery, comprising:

8. 8. The process according to claim 7, wherein the removal of water is carried out by a solid-liquid separation process.

9. A particulate cathode active material having an average particle size (D50) in the range of 2 to 16 μm, the cathode active material having a composition Li 1+x T.M. 1-x O 2 wherein x is in the range of 0.1 to 0.2, TM is a combination of elements according to general formula (II), and the metal moiety has the general formula: (Ni a Co b Mr c ) 1-d-e M 1 d M 2 e (II) (wherein a is in the range of 0.20 to 0.40; b is in the range of 0 to 0.15; c is in the range of 0.50 to 0.75; d is in the range of 0 to 0.015; e is in the range of 0 to 0.015; M 1 is selected from Al, Ti, Zr, Mo, Fe, Nb, and Mg; M 2 is selected from Al, Ti, Zr, Mo, Fe, Nb, B, W, and Mg; a + b + c = 1.0) The composite oxide has a thickness of 0.5 m 2 / g to 10m 2 / g range (BET), and at least 2.7 m 2 / g of press density of the cathode active material.

10. 10. The cathode active material of claim 9, wherein the structural distortion obtained by the Rietveld method for the reflection peak between 29.8° and 30.6° in the corresponding X-ray diffraction pattern using Mo-Kα radiation is 0.8% or less.

11. (1) at least one substance according to claim 9 or 10, (2) carbon in a conductive state, and (3) Binder An electrode comprising:

Citation Information

Patent Citations

  • Positive electrode active material for lithium secondary battery, method for producing same, and lithium secondary battery

    EP3486980A1

  • Nickel-manganese-based double hydroxide, its production and raw material for anode active material for lithium secondary cell

    JP1998081521A

  • Method for producing nickel-manganese composite oxyhydroxide

    JP2017178701A

  • Transition metal-containing hydroxide, and method for producing lithium-containing composite oxide

    WO2017135415A1

  • Positive electrode active material for non-aqueous electrolyte secondary battery, transition metal hydroxide precursor, method for production of transition metal hydroxide precursor, method for production of positive electrode active material for non-aqueous electrolyte secondary battery, positive electrode for non-aqueous electrolyte secondary battery, and non-aqueous electrolyte secondary battery

    WO2019117281A1